Doctor-patient relationship: main barriers and how to overcome them - Santiago, Luiz Miguel (2024)
There are several barriers to a sound doctor-patient relationship (DPR) development. This study aimed to review and summarize the literature on DPR barriers and to discuss possible ways to improve it, overcoming problems. A narrative literature revision was performed, reading title and abstract, of a total of 917 articles, 156 selected for complete reading out of which 67 were included in this review. The barriers to good DPR can be divided into four main categories: doctor-related, patient-related, doctor and patient-related, and external factors related. It is possible to intervene in several of these obstacles through medical student and doctor formation in communication and empathy, public health literacy amelioration, and organizational and procedural health facilities improvement. More quantitative and qualitative investigation is deemed necessary to reinforce the evidence and empirical knowledge about DPR.